2010
DOI: 10.1111/j.1601-0825.2010.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Somesthetic, gustatory, olfactory function and salivary flow in patients with neuropathic trigeminal pain

Abstract: All groups showed abnormal thresholds of gustation and olfaction; somesthetic findings were discrete in ITN and more common in PHN and BMS; central mechanisms of balance of sensorial inputs might be underlying these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
22

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 19 publications
4
65
0
22
Order By: Relevance
“…Thermal testing 14 was performed using the Thermosensi II electric test device (Functional Neurosurgery Division -Hospital das Clínicas, College School, São Paulo University, Brazil). The baseline temperature was 32ºC, and the contact square area of the thermode was 10x10 mm.…”
Section: Thermal Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal testing 14 was performed using the Thermosensi II electric test device (Functional Neurosurgery Division -Hospital das Clínicas, College School, São Paulo University, Brazil). The baseline temperature was 32ºC, and the contact square area of the thermode was 10x10 mm.…”
Section: Thermal Detectionmentioning
confidence: 99%
“…Mechanical/tactile and pain perception Touch perception 14 was assessed using a set of standardized vonFrey filaments with rounded tips of 0.5 mm diameter (g/mm 2 ) -IITC, WoodlandHills, USA. The mechanical pain detection was performed with standard pinpricks with 24 mm of length and 0.40 mm of diameter applied with an electronic device (g/mm 2 ) -Micromar ® , Diadema, São Paulo, Brazil.…”
Section: Thermal Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of previous findings that pain was associated with elevated olfactory thresholds in the absence of diabetes [43], Brady et al [19] sought to assess the potential impact of neurological pain caused by diabetic peripheral neuropathy on olfactory function. The study showed that those with neuropathic pain experienced loss of general olfaction, and had reduced odour detection thresholds, reduced discrimination between odour qualities, reduced odour identification, and increased thresholds for odour intensity [19], in line with some previous findings [13,14].…”
Section: Olfactory Dysfunction and Diabetes Complicationsmentioning
confidence: 99%
“…It has been more recently supported by many clinical articles showing abnormal gustative and olfactory functions in patients with orofacial neuropathic pain. 11,31 There is ample evidence of sensorial interaction between the trigeminal gustative and olfactory systems, which can be demonstrated by the convergence of inputs at the solitary tract, at the trigeminal complex, and in other subcortical areas. MVD is known as a procedure with little impact on facial sensitivity and few numbness complaints.…”
mentioning
confidence: 99%